2013
DOI: 10.1186/1742-2094-10-40
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin inhibits LPS-induced release of IL-6 from mouse dopaminergic neurones

Abstract: Background: Ghrelin is an orexigenic stomach hormone that acts centrally to increase mid-brain dopamine neurone activity, amplify dopamine signaling and protect against neurotoxin-induced dopamine cell death in the mouse substantia nigra pars compacta (SNpc). In addition, ghrelin inhibits the lipopolysaccharide (LPS)-induced release of pro-inflammatory cytokines from peripheral macrophages, T-cells and from LPS stimulated microglia. Here we sought to determine whether ghrelin attenuates pro-inflammatory cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…Ghrelin can cross the blood-brain barrier and act bidirectionally in the periphery and in the brain. In addition to its well-known role as a regulator of energy balance and food intake, Ghrelin may be involved in several brain mechanisms (Méquinion et al, 2013), many of those are altered in mood disorders as circadian rhythms (Kluge et al, 2013) and neuroinflammation (Miyake and Yamamura, 2009;Beynon et al, 2013). All these evidences indicated that an imbalance in Glucagon, GLP-1, GIP and Ghrelin levels might play a role in the pathogenesis of BD and in the mechanism causing the comorbidity between mood and metabolic disorders (Czepielewski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin can cross the blood-brain barrier and act bidirectionally in the periphery and in the brain. In addition to its well-known role as a regulator of energy balance and food intake, Ghrelin may be involved in several brain mechanisms (Méquinion et al, 2013), many of those are altered in mood disorders as circadian rhythms (Kluge et al, 2013) and neuroinflammation (Miyake and Yamamura, 2009;Beynon et al, 2013). All these evidences indicated that an imbalance in Glucagon, GLP-1, GIP and Ghrelin levels might play a role in the pathogenesis of BD and in the mechanism causing the comorbidity between mood and metabolic disorders (Czepielewski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown if TLR4 agonists activate AKT or GSK3 signaling in SN4741 cells, as they do in myeloid cells [44,45]. However, LPS induces IL-6 production and NF-κB activation in the SN4741 cells [46].…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown if TLR4 agonists activate AKT or GSK3 signaling in SN4741 cells, as they do in myeloid cells [44,45]. However, LPS induces IL-6 production and NF-κB activation in the SN4741 cells [46]. Recent studies showed that monocytes, macrophages, DCs, and microglia when preexposed to recombinant Wnt3a and Wnt5a displayed phenotypic changes upon subsequent TLR stimulation, including impaired proinflammatory cytokine expression, elevated IL-10 production, and NF-κB p50-homodimers [21,[24][25][26].…”
mentioning
confidence: 99%
“…30 Ghrelin, vagus nerve stimulation, glutamine, propofol, and Nrf2 use different mechanisms to regulate TNF-a. For example, ghrelin binds the growth hormone secretagogue receptor (GHS-R) on immune cells and inhibits PAMPinduced release of TNF-a, 31 and vagus nerve stimulation promotes the release of acetylcholine (ACh) by efferent vagus nerves to inhibit the production of TNFa by acetylcholine receptor (AChR)-expressing immune cells. 32 TNF-a expression in mammals is induced by Toll-like receptor (TLR) signaling pathways in macrophages and other cytokine-producing cells that are part of the defense mechanism provided by the innate immune response.…”
Section: Tbi Activates a Feedback Loop That Enhances Intestinal Permementioning
confidence: 99%